Pengaruh Self-Compassion, Religiusitas, Support Group Dan Pendapatan Terhadap Subjective Well-Being Orang Tua Anak Tunagrahita - Risa Dwi Ratnasari; Neneng Tati Sumiati (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2017)
Subjective well-being (SWB) is an evaluation of a person's cognitive and affective life. Evaluation of one's life in subjective well-being includes a positive emotional reaction to the occurrence in life, as well as the lack of negative emotional charge of cognition ratings on satisfaction and fulfillment in life (Diener, Lucas, & Oishi, 2005). This study was condu cted to determine the influence of self-compassion, religiosity, support group and pendapatan on subjective well-being of parents of children with mental retardation. Researcher adapting various instrument such as Diener's SWB instrument (1985; 2010), Neff's self-compassion instrument (2003), and Huber’s religiosity instrument (2012). The research method used a non-probability sampling with accidental sampling technique. Participants in this study amounted to 209 parents. The researcher use Confirmatory Factor Analysis (CFA) as construct validity test. The results showed that the four dimensions, namely self-compassion, religiosity,support group and pendapatan has a significant effect on subjective well-being of parents who have children with mental retardation. The proportion of the overall independent variables towards SWB amounted to 28.8% with four significant variables that self-compassion, religiosity in aspects of religious knowledge, religious experience and household income. Subjective Well-Being (SWB) adalah evaluasi kognitif dan afektif seseorang terhadap kehidupannya. Evaluasi kehidupan seseorang dalam subjective well-being mencakup reaksi emosi positif terhadap kejadian dalam hidup, rendahnya muatan emosi negatif sebagaimana penilaian kognisi atas kepuasan dan pemenuhan hidup (Diener, Lucas, & Oishi, 2005). Penelitian ini dilakukan untuk mengetahui pengaruh self-compassion, religiusitas, affiliasi support group dan pendapatan terhadap subjective well-being orangtua yang memiliki anak dengan tunagrahita. Peneliti mengadaptasi instrumen SWB diener (1985; 2010), untuk self-compassion mengadaptasi instrumen Neff (2003), dan untuk religiusitas mengadaptasi instrumen Hubber (2012). Metode penelitian menggunakan non-probability samplingdengan teknik accidental sampling.Partisipan dalam penelitian ini berjumlah 209 orang tua.Uji validitas konstruk menggunakan tekhnik CFA. Hasil penelitian menunjukan bahwa empat dimensi yakni self-compassion, religiusitas (pengetahuan keagamaan, pengalaman keagamaan), affiliasi support group dan pendapatan memiliki pangaruh yang signifikan terhadap subjective well-being orangtua yang memiliki anak dengan tunagrahita. Proporsi independent variable secara keseluruhan terhadap SWB adalah sebesar 28.8% dengan empat variabel signifikan yakni self-compassion, religiusitas di aspek pengetahuan keagamaan, pengalaman keagamaan dan pendapatan rumah tangga. DOI: 10.15408/jp3i.v6i1.8153